HYPOLIPIDEMIC THERAPY IN PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE IN 2004-2010 ACCORDING TO THE PROGNOZ IBS REGISTER - S. N. Tolpygina; Yu. N. Polyanskaya; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To evaluate the frequency of prescription, efficacy and patients adherence to statin therapy in a cohort of patients with ischemic heart disease (IHD), confirmed by coronary angiography data, during the period from 2004 to 2010 based on the data from the PROGNOZ IBS register.Material and methods. The PROGNOZ IBS register database was used in the study. The data of 550 patients from a cohort of patients with the confirmed IHD, who had undergone coronary angiography from 2004 to 2008 (303 of them were on the follow-up visit) were included in the final analysis.Results. Low frequency of statins prescription in patients with stable IHD prior to hospitalization in 2004-2007 and a significant improvement of its quality during the stay in a specialized cardiology unit were revealed in the PROGNOZ IBS register. The frequency of statin prescription at discharge increased from 10% to 85.5% (in most cases original drugs were used), but the prescribed doses were usually inadequate. Target blood lipid levels were not achieved in the majority of patients. The level of low density cholesterol <2.5 mmol/L at discharge was present in 6.3% of the patients (the short period of hospitalization insufficient for the achievement of statins maximum effect should be taken into consideration). 67% of patients had good adherence to lipid-lowering therapy 3.9 years after the admission, however, the original drugs had been replaced by a variety of generics in most patients. The efficacy of the therapy was inadequate: the target levels of total cholesterol (<4.5 mmol/L) and low density cholesterol (<2.5 mmol/L) were achieved in 40% of patients, of low density cholesterol (<2.0 mmol/l) - in 15.8%.Conclusion. Low frequency of statins prescription in patients with stable IHD before the admission to the hospital, its significant growth during the stay and its reduction after the discharge were revealed. The treatment efficacy was low at all stages of the observation. Patients' adherence to statin therapy in the outpatient setting remains inadequate.